ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT BELI FASHION PADA SOCIAL-COMMERCE DI KOTA BATAM - Rovina, Rovina; Saputra, Suyono (ITB AAS Indonesia Surakarta, 2024)
The aim of this research is to see what impact the influence of fashion brand purchase intentions from information, eom and price through trust and purchase intention has on e-commerce. This research was processed through distributing questionnaires. The sample in this research is people who have subscribed to video streaming on the Instagram and Facebook platforms. The population in this research is people who live in Batam City, who have bought foreign fashion brands through Social Commerce such as Instagram and Facebook. In this study, the Hair et al formula was used because the population of foreign fashion brand buyers in Batam City was unknown, therefore one question was multiplied by 10, where the required target respondents were 220 using primary data. The results of this research state that there is a significant positive influence of information on trust, purchase intention, Ewom on trust, price on trust.